Services for reuse and repair – The arrangement between touchpoints and relational infrastructures - Chiara Olivastri; Giovanna Tagliasco (Agathón)
Regarding the circular economy and strategies, this paper describes the research/action project related to establishing a new Reuse and Repair Centre within the Surpluse network. The paper aims to illustrate the design choices of the setup, considered as a touchpoint for the definition of a network (service) and to facilitate interactions between displayed second-hand items and users. The proposed model becomes a format to be adapted in the creation of new future centres and the implementation of existing ones; furthermore, it aims to incentivise behaviours in favour of sustainability strategies and raise awareness among citizens for active participation within and in favour of the circular economy, co-designing relationships among the various stakeholders involved.